A pleiotropic effect of the APOE gene: association of APOE polymorphisms with multibacillary leprosy in Han Chinese from Southwest China. (1st April 2018) - Wang, D.; Zhang, D.‐F.; Li, G.‐D.; Bi, R.; Fan, Y.; Wu, Y.; Yu, X.‐F.; Long, H.; Li, Y.‐Y.; Yao, Y.‐G.
Summary: Background: Patients with leprosy have a very low risk of Alzheimer disease (AD) and β‐amyloid (Aβ) deposition is significantly lower in the brain tissue of elderly patients with leprosy compared with age‐matched controls. Apolipoprotein E (ApoE) plays a critical role in lipid metabolic pathways and in the brain, facilitating the proteolytic clearance of Aβ. We hypothesized that APOE confers risk of leprosy as lipid metabolism is involved in Mycobacterium leprae infection. Objectives: To investigate the potential genetic associations between APOE and leprosy in two independent Chinese case–control cohorts from the Yuxi and Wenshan prefectures, Yunnan Province of Southwest China. Methods: Five APOE single‐nucleotide polymorphisms (SNPs) were analysed in 1110 individuals (527 patients and 583 controls) from the Yuxi prefecture using a SNaPshot assay. Genetic variations in the entire APOE exons were screened in 1788 individuals (798 patients and 990 controls) from the Wenshan prefecture using next‐generation sequencing technology. Results: The AD‐associated SNPs rs405509 and rs439401 increased the risk of leprosy per se and multibacillary leprosy ( P < 0·005), but the APOE ‐ε4 allele did not. The SNPs rs405509 and rs439401 were cis expression quantitative trait loci (eQTL) for APOE expression in human skin. Differential APOE mRNA expression was observed in skin lesions of patients with type I reaction leprosy and those with multibacillary leprosy. APOE and related lipid genes are involved in an interaction network with leprosy susceptibility genes. Conclusions: The APOE gene is associated with leprosy, most likely by regulating lipid‐metabolism‐related genes.